1991
DOI: 10.1093/nar/19.21.5907
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct human DNA diesterases that hydrolyze 3′-blocking deoxyribose fragments from oxidized DNA

Abstract: Mammalian cells were investigated for enzymes that help correct oxidative damages in DNA. We focused on 3'-repair diesterases, which process DNA ends at oxidative strand breaks by removing 3'-blocking fragments of deoxyribose that prevent DNA repair synthesis. Two enzymes were found in a variety of mouse, bovine and human tissues and cultured cells. The two activities were purified to differing degrees from HeLa cells. One enzyme had the properties of the known HeLa AP endonuclease (Mr approximately 38,000, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
175
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(192 citation statements)
references
References 33 publications
17
175
0
Order By: Relevance
“…APE1 is the major AP endonuclease in human cells and accounts for 95% of the total AP endonuclease activity, and is essential for the protection of cells against the toxic effects of several classes of DNAdamaging agents. [7][8][9][10] APE1 is active in both and interacts with several proteins including 8-oxoguanine DNA glycosylase , X-ray cross-complementing-1 , proliferating cell nuclear antigen, flap endonuclease 1 and polymerase b. 32 In addition to AP endonuclease activity, APE1 also possesses 3 0 -phosphodiesterase, 3 0 -phosphatase and 3 0 -5 0 -exonuclease functions specific for the 3 0 termini of internal nicks and gaps in DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APE1 is the major AP endonuclease in human cells and accounts for 95% of the total AP endonuclease activity, and is essential for the protection of cells against the toxic effects of several classes of DNAdamaging agents. [7][8][9][10] APE1 is active in both and interacts with several proteins including 8-oxoguanine DNA glycosylase , X-ray cross-complementing-1 , proliferating cell nuclear antigen, flap endonuclease 1 and polymerase b. 32 In addition to AP endonuclease activity, APE1 also possesses 3 0 -phosphodiesterase, 3 0 -phosphatase and 3 0 -5 0 -exonuclease functions specific for the 3 0 termini of internal nicks and gaps in DNA.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The human apurinic/apyrimidinic endonuclease (APE1) is an essential enzyme in the base excision repair (BER) pathway, which is responsible for the repair of oxidative and alkylation DNA damage. APE1 accounts for nearly all of the abasic site cleavage activity in most cultured human cell lines, [7][8][9][10] and is essential for the protection of cells against the toxic effects of several classes of DNA-damaging agents. Moreover, APE1 has 3 0 -repair diesterase or phosphatase activity, albeit at 200-fold lower than its AP endonuclease activity.…”
Section: Introductionmentioning
confidence: 99%
“…The initial work on the purified mouse, bovine, and human AP endonuclease found that the mammalian protein exhibited not only a powerful class II AP site incision activity, but also the ability to excise 3¢-damages, such as 3¢-phosphates, 3¢-phosphoglycolate esters, and 3¢-deoxyribose fragments (27,173,182,183). These 3¢-end blocking groups prevent primer extension by a DNA polymerase or nick ligation by a DNA ligase, and, thus, have the potential to promote chromosome instability as unrepaired strand breaks.…”
Section: ¢-Repair Diesterasementioning
confidence: 99%
“…In view of the amount of Ape1 present in most cell types (Cappelli et al, 2001;Chen et al, 1991), it appeared likely that most dL residues would be 5' cleaved by the enzyme before AP lyases would have the opportunity to react. The next enzyme of BER, Polb, would then be poised to mediate excision of the abasic residue.…”
Section: Dangerous Liaisons: Enzyme Trapping By DLmentioning
confidence: 99%